2013
DOI: 10.1063/1.4775680
|View full text |Cite
|
Sign up to set email alerts
|

Half-metallic ferromagnetism in wurtzite ScM (M=C, Si, Ge, and Sn): Ab initio calculations

Abstract: Using the full potential linearized augment plane wave method with the modified Becke and Johnson (mBJ) potential, the half-metallicity and electronic structure for the wurtzite ScM (M = C, Si, Ge, and Sn) compounds are investigated. The ScM series compounds are found to be excellent half-metallic ferromagnets (HMFs) with large half-metallic gaps (0.76–0.33 eV). The magnetic moments are 2.00 μB per cell, and p-d hybridization mechanism plays crucial role in forming the half-metallic ferromagnetism. The ferroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…For electronic structure calculations, the modified Becke-Johnson exchange potential is used due to significantly improved band gap results. The mBJ exchange correlation potential as an orbital independent, semi-local exchange correlation potential has been proved to produce accurate gaps for wide band gap insulators, sp semiconductors, 3d transition-metal oxides [28,32] half-metallicity [33,34] and doped semiconductors systems [35]. To get the total energy convergence, an energy cut-off parameter RK max (R is the average radius of the muffin-tin (MT) spheres and K max is the cut-off for the wave function basis) is discussed as 6.…”
Section: Methods Of Calculationmentioning
confidence: 99%
“…For electronic structure calculations, the modified Becke-Johnson exchange potential is used due to significantly improved band gap results. The mBJ exchange correlation potential as an orbital independent, semi-local exchange correlation potential has been proved to produce accurate gaps for wide band gap insulators, sp semiconductors, 3d transition-metal oxides [28,32] half-metallicity [33,34] and doped semiconductors systems [35]. To get the total energy convergence, an energy cut-off parameter RK max (R is the average radius of the muffin-tin (MT) spheres and K max is the cut-off for the wave function basis) is discussed as 6.…”
Section: Methods Of Calculationmentioning
confidence: 99%
“…Figure 2 summarizes the procedure in the form of a flowchart. Both the mBJ and HSE functionals have been known to produce more accurate bandgap than the standard GGA, and yield values close to experiments 49‐51 . For the thermoelectric properties, we used semi‐classical Boltzmann transport theory implemented in the Boltztrap code 52 .…”
Section: Theoretical Modelsmentioning
confidence: 99%
“…It is found that the cohesive energies E coh are −16.561 and −12.043 eV for (CaC) 1 /(SiC) 1 and (KC) 1 /(SiC) 1 , respectively, indicating that the Ca‐ and K‐embedded systems are both energetically stable. Consequently, the syntheses would be endothermal reactions and the compounds once synthesized should be stable thermodynamically .…”
Section: Resultsmentioning
confidence: 99%